The More You Have, The More You Lose: Criminal Justice Involvement, Ascribed Socioeconomic Status, and Achieved SES. (10th March 2017) - Dennison, Christopher R; Demuth, Stephen
Abstract: In the present study, we examine the relationship between involvement in the criminal justice system and achieved socioeconomic status (SES), as well as the moderating effect of ascribed SES. Using data from the National Longitudinal Study of Adolescent to Adult Health, we find a nonlinear relationship between criminal justice involvement and achieved SES, such that deeper involvement leads to increasingly negative consequences on achieved SES. Furthermore, those coming from the highest socioeconomic backgrounds are not "protected" from the deleterious consequences of system involvement, but instead experience the greatest declines in achieved SES relative to where they started. In contrast, the effect of criminal justice involvement for those from below average ascribed SES is not significant. Our findings reinforce how normal such experiences are for people with the fewest resources, and also how system involvement inevitably destroys human capital, undermines future life chances, and ultimately promotes a "rabble" class.